Effect of oxygen post-annealing at the critical parameters of mercury cuprates - (:unkn) unknown (ELSEVIER SCIENCE BV, 2000)
After being prepared by quenched melt growth technique (QMG), the mercury-1223 superconductors were annealed with oxygen for several times. According to the DC SQUID measurements performed at 10 G, it was determined that the Meissner onset temperature, T-c, decreased by 10 K (from 136 to 126 K). The critical current densities, J(c), have been deduced from hysteresis loops, and were calculated by using the Bean Critical State model, at three different temperatures: J(c) congruent to 2 X 10(7) A/cm(2) at 5 K and 0.25 T, which is about three times less than the value obtained without post-oxygen annealing; J(c) congruent to 5.8 X 10(4) A/cm(2) at 77 K and 0.02 T, which is two orders of magnitude smaller than it used to be; J(c) congruent to 3.6 X 10(4) A/cm(2) at 90 K and 0.02 T. Moreover, it was determined that the superconducting materials are thermally stable above 90 K. The decrease in the critical parameters has been attributed to the formation of some mesoscopic defects that must be enhanced by further oxygen annealing. (C) 2000 Elsevier Science B.V. All rights reserved.
Keywords: doping dependency; critical current density; magnetization; synthesis